2021
DOI: 10.3390/cells10102729
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AhR in the Hallmarks of Brain Aging: Friend and Foe

Abstract: In recent years, aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor, has been considered to be involved in aging phenotypes across several species. This receptor is a highly conserved biosensor that is activated by numerous exogenous and endogenous molecules, including microbiota metabolites, to mediate several physiological and toxicological functions. Brain aging hallmarks, which include glial cell activation and inflammation, increased oxidative stress, mitochondrial dysfunction, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 144 publications
0
24
0
Order By: Relevance
“…AhR mediates the effects of these substances through the arachidonic acid pathway, cell differentiation, intercellular adhesion interactions, cytokine expression, and mucin production. Human bronchial epithelial cells are reported to express AhR, and AhR activation induces mucin production via reactive oxygen species [ 277 , 279 , 282 , 283 , 284 ].…”
Section: Ahr In the Pathogenesis Of Diseases Related To Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…AhR mediates the effects of these substances through the arachidonic acid pathway, cell differentiation, intercellular adhesion interactions, cytokine expression, and mucin production. Human bronchial epithelial cells are reported to express AhR, and AhR activation induces mucin production via reactive oxygen species [ 277 , 279 , 282 , 283 , 284 ].…”
Section: Ahr In the Pathogenesis Of Diseases Related To Oxidative Stressmentioning
confidence: 99%
“…AhR activation can influence the inflammatory phase in both asthma and chronic obstructive pulmonary disease through inflammatory and resident cells in the lungs [ 282 , 284 ]. The relation between AhR function and airway inflammation in the initial phase is important not only in chronic obstructive pulmonary disease but also in asthma.…”
Section: Ahr In the Pathogenesis Of Diseases Related To Oxidative Stressmentioning
confidence: 99%
“…Recently, the AhR, an ancient protein that possesses highly conserved functions across various species, has been associated with brain aging and age-associated diseases [18,42]. Apart from its well-described role in xenobiotic metabolism, AhR plays a critical role in the developing nervous system of invertebrates and vertebrates.…”
Section: Fig 3 Efferent and Afferent Control Of Cardiac Function [43]mentioning
confidence: 99%
“…GH also possesses XRE sequences in its promoter, for which AhR can compete to regulate its expression [ 223 , 224 ]. Beta-naphthoflavone (BNF), an agonist of AhR, can disrupt several genes involved in the neuroendocrine regulation of stress [ 225 , 226 ]. Overall, most studies have shown AhR to affect the HPG axis, while the effects on GH, TSH, and ACTH are still not clear [ 227 , 228 , 229 , 230 ].…”
Section: Xenobiotics Modulating Aryl Hydrocarbon Receptor To Regulate...mentioning
confidence: 99%
“…Many exogenous AhR ligands such as TCDD and PAHs can cross the blood brain barrier (BBB) to mediate AhR action in the brain. Likewise, many endogenous AhR ligands derived from tryptophan metabolites such as indoxyl-3-sulfate (I3S), indole-3-carbinol (I3C) and FICZ also cross the BBB via gut–brain axis to modulate AhR activity in the brain in response to various environmental and metabolic cues [ 226 , 235 ]. Their ubiquitous distribution, lipid solubility and long-lasting half-life, promote bioaccumulation of the compounds throughout the food chain by depositing in lipid-heavy tissues such as adipose and brain [ 236 , 237 , 238 ].…”
Section: Xenobiotics Modulating Aryl Hydrocarbon Receptor To Regulate...mentioning
confidence: 99%